2013
DOI: 10.1021/es3052069
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Environmental Implications of Photo-Transformation Products of Trenbolone Acetate Metabolites

Abstract: Despite the widespread use of the anabolic androgen trenbolone acetate (TBA) in animal agriculture, evidence demonstrating the occurrence of TBA metabolites such as 17β-trenbolone (17β-TBOH), 17α-trenbolone (17α-TBOH), and trendione (TBO) is relatively scarce, potentially due to rapid transformation processes such as direct photolysis. Therefore, we investigated the phototransformation of TBA metabolites and associated ecological implications by characterizing the photoproducts arising from the direct photolys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
69
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(74 citation statements)
references
References 46 publications
5
69
0
Order By: Relevance
“…Recent research has shown that cycling of trenbolone metabolites may occur in surface waters either due to diurnal light progression and/or due to differences in light penetration as water circulates between depths. These studies have documented a regeneration of 17β-Tb, 17α-Tb, and Td from structurally similar photoproducts (12-hydroxy-trenbolone, 10,12-dihydroxy-trenbolone, and trenbolone-11,12-dialdehyde) during periods of darkness with significant implications for trenbolone bioavailability in natural systems (Oliver et al, 2010;Kolodziej et al, 2013;Qu et al, 2012). However, it is important to note that these studies evaluated surface water systems with low suspended solids.…”
Section: β-Trenbolone Fate and Bioavailability In Aquatic Systemsmentioning
confidence: 99%
“…Recent research has shown that cycling of trenbolone metabolites may occur in surface waters either due to diurnal light progression and/or due to differences in light penetration as water circulates between depths. These studies have documented a regeneration of 17β-Tb, 17α-Tb, and Td from structurally similar photoproducts (12-hydroxy-trenbolone, 10,12-dihydroxy-trenbolone, and trenbolone-11,12-dialdehyde) during periods of darkness with significant implications for trenbolone bioavailability in natural systems (Oliver et al, 2010;Kolodziej et al, 2013;Qu et al, 2012). However, it is important to note that these studies evaluated surface water systems with low suspended solids.…”
Section: β-Trenbolone Fate and Bioavailability In Aquatic Systemsmentioning
confidence: 99%
“…Accordingly, we previously identified the structure and bioactivity of TBA metabolite photoproducts, showing that 17β-TBOH undergoes rapid photohydration (13) to yield 12,17-dihydroxy-estra-5(10),9(11)-diene-3-one (or simply 12-hydroxy-17β-TBOH) (14, 15). An analogous C12-hydroxylated photoproduct was identified for TBO (15), whereas 17α-TBOH yields both major C12 [12-hydroxy-17α-TBOH (15)] and minor C5 (5-hydroxy-17α-TBOH) hydroxylated photoproducts (supplementary text and figs.…”
mentioning
confidence: 99%
“…On the basis of observations in Qu et al 1 , photolysis of 17a-TBOH was assumed to yield 90% revertible products (that is, hydroxy-17a-TBOH) and 10% other products not subject to reversion and assumed non-bioactive (for example, species with a substantially modified structure, such as the 11,12-dialdehyde product we previously reported 15 ). All other parameters were assumed constant in space and time to isolate the effect of the reversion process on results.…”
Section: Methodsmentioning
confidence: 99%
“…One benefit of our modelling approach is that we can explore fate and risk scenarios that might otherwise be too difficult to assess via traditional approaches wholly reliant on demanding and expensive analytical measurements. For example, a scenario that complicates risk management for TBA metabolites is that their photoproducts seem to retain some aspects of bioactivity distinct from their parent metabolites 15 . Thus, confining ecological risk considerations only to the known bioactivity of 17a-TBOH would underestimate the ecological hazard posed by the mixture of parent and product bioactivity.…”
Section: Reversion Increases 17a-tboh Persistence In Stream Networkmentioning
confidence: 99%
See 1 more Smart Citation